PVA-Based Mixed Matrix Membranes Comprising ZSM-5 for Cations Separation - Sheng, Fangmeng (Membranes (Basel), 2020)
The traditional ion-exchange membranes face the trade-off effect between the ion flux and perm-selectivity, which limits their application for selective ion separation. Herein, we amalgamated various amounts of the ZSM-5 with the polyvinyl alcohol as ions transport pathways to improve the permeability of monovalent cations and exclusively reject the divalent cations. The highest contents of ZSM-5 in the mixed matrix membranes (MMMs) can be extended up to 60 wt% while the MMMs with optimized content (50 wt%) achieved high perm-selectivity of 34.4 and 3.7 for H(+)/Zn(2+) and Li(+)/Mg(2+) systems, respectively. The obtained results are high in comparison with the commercial CSO membrane. The presence of cationic exchange sites in the ZSM-5 initiated the fast transport of proton, while the microporous crystalline morphology restricted the active transport of larger hydrated cations from the solutions. Moreover, the participating sites and porosity of ZSM-5 granted continuous channels for ions electromigration in order to give high limiting current density to the MMMs. The SEM analysis further exhibited that using ZSM-5 as conventional fillers, gave a uniform and homogenous formation to the membranes. However, the optimized amount of fillers and the assortment of a proper dispersion phase are two critical aspects and must be considered to avoid defects and agglomeration of these enhancers during the formation of membranes.